Remote assessment of music perception in pediatric cochlear implant recipients. - Yüksel, Mustafa; Küçük Ceyhan, Ayşenur; Terlemez, Şengül (International Journal of Audiology, 2025)
Objective: The primary objective of this study was to explore the feasibility of remotely assessing music perception in paediatric cochlear implant (CI) recipients. Pitch direction discrimination (PDD) and timbre recognition (TR) tests were administered remotely. We aimed to provide insights into the potential benefits and challenges of remote assessments. Design: The study was exploratory in nature. All participants underwent remote assessments for the PDD and TR tests. Eight participants completed both online and face-to-face tests. Supervising parents in remote tests completed the System Usability Scale (SUS). Study Sample: A cohort of 27 children with CI, averaging 11.19 years of age, participated in this study. Results: In the online condition, the average PDD score was 3.29 semitones (st), the TR score was 37.86%, and the average duration for PDD and TR testing was 9.98 and 6.18 minutes, respectively. Face-to-face sessions had an average PDD score of 3.00 st, a TR score of 32.81% and durations of 10.20 and 5.42 minutes for PDD and TR tests, respectively. The SUS score averaged 64.04. Conclusion: These findings contribute to the growing body of knowledge supporting the integration of remote assessments in audiological practices.